Curcumin Improves Delayed Onset Muscle Soreness and Postexercise Lactate Accumulation. (23rd August 2021) - Mallard, Alistair R.; Briskey, David; Richards, BExSSc, Andrew; Rao, Amanda
Abstract: The efficacy of curcumin supplementation is traditionally limited due to its poor bioavailability. Despite this, curcumin has previously been shown to improve biomarkers of muscle damage. The addition of a novel drug delivery system that improves bioavailability could improve exercise recovery. The purpose of this randomized double-blind placebo-controlled study was to assess the effect of curcumin (combined with LipiSperse) when consumed as a drink on exercise recovery in recreationally trained healthy males aged 18–35 yrs. The study included 28 young healthy males with strength training experience. The participants undertook lower limb resistance exercise to exhaustion. Fourteen participants received curcumin dispersed in water pre and postexercise and 14 received a matched placebo drink. Pain (visual analogue scale), thigh circumference (TC), lactate, creatine kinase, lactate dehydrogenase, high sensitivity C-reactive protein, myoglobin, interleukin-6, interleukin-10, and tumor necrosis factor-alpha were assessed pre, postexercise and 1, 2, 3, 24, 48, and 72 h postexercise. There was less appearance of postexercise capillary lactate in the curcumin group compared to placebo (7.4 vs 8.8 mmol/L). The placebo group rated overall muscle pain as higher compared to the curcumin group at 48- and 72-h postexercise. TC was reduced in the curcumin group compared to the placebo group at 24- and 48-h postexercise. The results suggest curcumin may facilitate a quicker return to exercise training and/or allow a higher training intensity than a placebo by reducing postexercise pain, modulating inflammatory pathways and reducing lactate accumulation in an exercising population.